Pro SharePoint 2010 Solution Development Combining .NET, SharePoint, and Office 2010 - Hild, Ed.; Wach, Chad.; SpringerLink (Online service) (Berkeley, CA : Apress, 2010)
This book takes a practical problem-solution approach to common business challenges. You$1 (Bll not only encounter interesting code samples, but also see how to combine these examples with the Microsoft collaboration platform$1 (Bs services. The book$1 (Bs solutions focus on using Visual Studio 2008 and its built-in Office development tools to construct the user interface layer. And solutions can interact with SharePoint as a service provider, taking advantage of SharePoint$1 (Bs many collaboration features like document repositories, collaboration sites, and search functions. This book is unique because it starts with challenges that end users deal with every day when using the Microsoft collaboration platform to support business processes. The solutions are presented as hypothetical business challenges of a fictional company. By presenting the examples in this context, author Ed Hild makes it easier to relate to the challenges and solution value. The goal of these examples is to build applications that apply the benefits of the Office desktop interface to the richness of SharePoint collaboration features. This book will help you develop real-world solutions to complex business problems and challenges.s
Office Business Applications -- SharePoint 2010: Overview and New Features -- SharePoint Development with Visual Studio 2010 -- Microsoft Office Overview for Developers -- Beyond the Spreadsheet -- Merging SharePoint List Data into Word Documents -- Automating Document Assembly -- Extending PowerPoint to Build a Presentation Based on Site Content -- Building a Presentation Server-Side within a Web Part -- Surfacing Line-of-Business Data in Outlook -- Site Provisioning Workflows -- Rapid SharePoint Application Development Using Access -- Using Visio Services to Visualize Data -- Building Mashups -- Realizing the Vision.
Keywords: Computer science; Computer Science; Programming Techniques